Scientific and applied principles of inventory of territorial communities lands in Ukraine - Butenko, E.; Prykhodko, M. (Land Management, Cadastre and Land Monitoring, 2024)
The article examines the process and stages of land inventory. The Resolution of the CMU dated June 5, 2019 No. 476 "Procedure for Land Inventory" was analyzed. The territory of a part of the settlement, which is subject to inventory, and the effectiveness of land resource management measures have been analyzed. The components and essence of land during the inventory were studied. Proposals for improving the scientific and applied principles of land inventory are offered.The land-resource potential and the efficiency of its use within the settlement, which is the object of the study, were investigated and studied.It is proposed to improve the scientific and applied principles of land inventory as a result of the establishment of security zones, restricted zones around regime-forming objects, and the establishment of the settlement boundary.The process of carrying out topographical and geodetic works, the types of surveys used for the inventory process were investigated. It is proposed to improve measures to save resources and time for work during the update of the cartographic base by combining surveying methods.The analysis of the data of the State Land Cadaster and the database of state acts of the self-governing body, which can increase the effective management of land and improve the state of land use, was carried out.The necessity of carrying out a land inventory in order to study land resources to simplify the land management and urban planning process, effective implementation of land management by creating an electronic resource with survey materials and the results of topographical and geodetic works is substantiated.Determined: boundaries of land plots based on the results of the inventory; boundaries of land plots with an assigned cadastral number; boundaries of lands granted ownership; boundaries of land plots used without documents certifying property rights to them; boundaries of lands not granted for ownership or use.It is proposed to improve the scientific and applied principles of land inventory, due to the creation of an electronic resource for the publication of the results of land management works, with the aim of increasing the investment attractiveness of the community, effective management of community lands and significantly simplifying the search for plots for various needs.
Keywords: land inventory; land resource potential; land resources; management efficiency; improvement; geoinformation system; settlement.